2003
DOI: 10.1002/ange.200250692
|View full text |Cite
|
Sign up to set email alerts
|

A Pseudorotaxane on Gold: Formation of Self‐Assembled Monolayers, Reversible Dethreading and Rethreading of the Ring, and Ion‐Gating Behavior

Abstract: Reversibles Ab‐ und Wiederauffädeln von Cucurbiturilmolekülen wird bei einer selbstorganisierten Monoschicht eines Pseudorotaxans auf Gold beobachtet. Je nach An‐ oder Abwesenheit eines Cucurbituril‐„Rades“ auf der „Achse“ blockiert oder ermöglicht die Monoschicht den Zugang elektroaktiver Spezies zur Elektrodenoberfläche (siehe Bild).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 51 publications
0
29
0
1
Order By: Relevance
“…Kim and co-workers have reported the functionalization of a gold surface with the pseudorotaxane CB [6]·41. [154] Surface plasmon resonance (SPR) studies have shown that SAMs comprising CB [6]·41 undergo reversible dethreading and rethreading of the CB [6] beads upon treatment with 0.1m NaOH followed by CB [6]. Cyclic voltametry measurements indicate that the SAM formed by pseudorotaxane CB [6]·41 constitutes an effective barrier to redox processes involving [Fe(CN) 6 ] 3À : a quasireversible redox wave is observed after dethreading.…”
Section: Catalysismentioning
confidence: 97%
“…Kim and co-workers have reported the functionalization of a gold surface with the pseudorotaxane CB [6]·41. [154] Surface plasmon resonance (SPR) studies have shown that SAMs comprising CB [6]·41 undergo reversible dethreading and rethreading of the CB [6] beads upon treatment with 0.1m NaOH followed by CB [6]. Cyclic voltametry measurements indicate that the SAM formed by pseudorotaxane CB [6]·41 constitutes an effective barrier to redox processes involving [Fe(CN) 6 ] 3À : a quasireversible redox wave is observed after dethreading.…”
Section: Catalysismentioning
confidence: 97%
“…Recent researches in the development of bioactive SAMs have tried to tackle the challenge of designing dynamic SAMs that could undergo on demand surface reactions under external stimuli. 3b, 11 Such smart surfaces provide unique switchable monolayers whose surface activities can be turned on only when needed. These smart surfaces may enable new applications in fields like controlled ligand immobilization, cell adhesion, and biochemical sensors.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Molecules capable to form SAMs generally consist of three essential parts: the headgroup that binds the ligand to the substrate, the tail group that constitutes the outermost surface of the monolayer film, and the spacer unit that separates the head and tail building blocks and drive the spontaneous molecular assembly, due to intermolecular interactions. Within this general concept, one can combine different moieties and terminal functionalities into simple rigid-rod-like molecules, complex architectures, or even molecular ''devices'', carrying active units which serve as, e.g., electrodes [7], biosensors [8], molecular machines [9,10], or molecular electronics components and devices [11,12].…”
Section: Introductionmentioning
confidence: 99%